DESIGN AND CONSTRUCTION OF A SIMPLE FATIGUE TESTING DEVICE FOR PUSH BUTTONS USING PNEUMATIC AND DC MOTOR SYSTEMS BASED ON PROGRAMMABLE LOGIC CONTROLLER - Hidayah, Alfi Noer; Zaenudin, Mohamad; Saleh, Yasya Khalif Perdana (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2026)
Button fatigue testing remains prohibitively expensive for SMEs due to commercial systems costing >5,000. This study develops a low-cost tester of less than 500, PLC-controlled using dual actuation systems (pneumatic and DC motor) to evaluate pushbutton durability under 100–300 g loads. The pneumatic system maintained extensive pressure stability of ±0.00 MPa at 0.04 MPa for 200 g testing but exhibited 20.64% load deviation due to compressor-induced 600 g transient spikes during reservoir refills. Alternatively, the DC motor system achieved high-precision 100 g testing at 270 rpm with 3.98% deviation with stable speed around 260–278 rpm but failed operationally at 540 rpm for 300 g loads due to vibration-induced signal disruption after cycle 277. Moreover, pneumatic actuation proved more suitable for loads lower than 200 g, completing 10,000 cycles despite load spikes, while a DC motor maintains stability at lower than 200 g with near-constant force below 500 rpm. This study establishes a clear implementation framework: pneumatic systems for production-line screening where ±20% deviation is acceptable per ISO 9241-410 and DC motor systems for calibration-grade testing requiring <5% deviation. The prototype bridges the affordability gap for SMEs and educational institutions, with future work targeting vibration dampeners and pressure accumulators to achieve ASTM E467-21 compliance.